Wellness = healthy nutrition + active life (Journal of Parents and Teachers, 2014)
The analysis of the food myths, junk food’s effects and cancerous diseases associated with poor nutrition give to the authors arguments to work in the concept of wellness in school.
Keywords: education; habits; nutrition; disease; wellness; school.